2019
DOI: 10.1136/heartjnl-2019-315422
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol septal ablation in patients with severe septal hypertrophy

Abstract: ObjectiveThe current guidelines suggest alcohol septal ablation (ASA) is less effective in hypertrophic obstructive cardiomyopathy (HOCM) patients with severe left ventricular hypertrophy, despite acknowledging that systematic data are lacking. Therefore, we analysed patients in the Euro-ASA registry to test this statement.MethodsWe compared the short-term and long-term outcomes of patients with basal interventricular septum (IVS) thickness <30 mm Hg to those with ≥30 mm Hg treated using ASA in nine Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…In particular, in clinical practice ASA is preferred to SM mainly in the elderly at high operative SM risk, who may have a different septal phenotype from non-elderly HCM patients at low operative SM risk. Indeed, non-elderly HCM patients at low SM risk may have a high-penetrance phenotype that is substantially different from age-dependent remodeled septal phenotype [ 8 , 10 , 70 , 71 , 72 , 73 ]. Thus, in the general population of HCM patients, the prevalence of ASA feasibility may differ.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in clinical practice ASA is preferred to SM mainly in the elderly at high operative SM risk, who may have a different septal phenotype from non-elderly HCM patients at low operative SM risk. Indeed, non-elderly HCM patients at low SM risk may have a high-penetrance phenotype that is substantially different from age-dependent remodeled septal phenotype [ 8 , 10 , 70 , 71 , 72 , 73 ]. Thus, in the general population of HCM patients, the prevalence of ASA feasibility may differ.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical myectomy has demonstrated excellent long-term efficacy and safety at selected high-volume centres with near-complete resolution of resting and inducible LVOT gradients. ASA showed similar perioperative mortality (about 1%) when compared to myectomy [136], although associated with a 10-15% rate of complete heart block, repeat procedures and increased risk of scar-related ventricular arrhythmias [137,138]. Moreover, ASA is dependent on coronary anatomy since 15% of patients had unsuitable septal perforators [139].…”
Section: Hocmmentioning
confidence: 99%
“…It has been recently demonstrated that in selected patients, with both the modest septum thickness (15-16 mm) and with severe septal hypertrophy, ASA was found effective and safe in the long-term follow-up. 1,7 LVOT obstruction depends largely on the length of mitral leaflets and submitral chords, papillary muscle abnormalities including their number, hypertrophy, localization, and possible direct attachment to anterior mitral leaflet or short interposition of chords. Evidence suggests some patients encounter obstruction not only in LVOT but also in the midventricular part, therefore the precise evaluation of obstruction is necessary, and adding magnetic resonance imaging or computer tomography of a heart is very valuable.…”
Section: Anatomical Considerationmentioning
confidence: 99%
“…ASA is described as an interventional procedure guided by myocardial contrast echocardiography and the first septal branch is considered as the usual target of alcohol injection. 1,[4][5][6][7][8] The morphological result of ASA should be similar to myectomy which is difficult to achieve in all patients because of anatomical variations of septal branches. A preprocedural computerized tomography coronary angiography could benefit in identifying the optimal septal (sub)branch.…”
Section: Have a Planmentioning
confidence: 99%
See 1 more Smart Citation